Decisions from Experience and the Effect of Rare Events in Risky Choice - Hertwig, Ralph; Barron, Greg; Weber, Elke U.; Erev, Ido (Psychological Science, 2004)
When people have access to information sources such as newspaper weather forecasts, drug-package inserts, and mutual-fund brochures, all of which provide convenient descriptions of risky prospects, they can make decisions from description. When people must decide whether to back up their computer's hard drive, cross a busy street, or go out on a date, however, they typically do not have any summary description of the possible outcomes or their likelihoods. For such decisions, people can call only on their own encounters with such prospects, making decisions from experience. Decisions from experience and decisions from description can lead to dramatically different choice behavior. In the case of decisions from description, people make choices as if they overweight the probability of rare events, as described by prospect theory. We found that in the case of decisions from experience, in contrast, people make choices as if they underweight the probability of rare events, and we explored the impact of two possible causes of this underweighting—reliance on relatively small samples of information and overweighting of recently sampled information. We conclude with a call for two different theories of risky choice.